The Role of Self-Esteem in Depression: A Longitudinal Study. Issue 2 (25th April 2018) - Hilbert, Sven; Goerigk, Stephan; Padberg, Frank; Nadjiri, Annekatrin; Übleis, Aline; Jobst, Andrea; Dewald-Kaufmann, Julia; Falkai, Peter; Bühner, Markus; Naumann, Felix; Sarubin, Nina
Abstract : Background: Based on the vulnerability model, several studies indicate that low self-esteem seems to contribute to depressive symptoms.Aims: The aim of this study was to treat depressive symptoms in a cognitive behavioural group therapy, focusing on the enhancement of self-esteem, and to explore co-variation in depressive symptoms and the level of self-esteem.Method: The Multidimensional Self-esteem Scale (MSWS) and the Beck Depression Inventory (BDI) were administered to 147 psychiatric in-patients with current depressive symptoms due to an affective disorder (major depression, bipolar I, dysthymia). Self-esteem was measured pre-treatment (t0 ) and post-treatment (t4, after 5 weeks of eight group sessions); the BDI was applied weekly. A linear mixed growth analysis was conducted to estimate the change in depressive symptoms including interactions with self-esteem.Results: Within the 5 weeks of group therapy, depressive symptoms showed a linear decline, which was stronger for patients with higher gains in self-esteem between t0 and t4 . Self-esteem at t0 was unrelated to the change in depression but predicted self-esteem at t4 .Conclusions: Treating depressive symptoms in a cognitive behavioural group therapy in a naturalistic setting might have a positive effect on the process of recovery. Moreover, depressive symptoms and level of self-esteem seemed to co-vary.